Mechanical characteristics of Hanfu apple at low temperature - Benhua, Zhang; Shujie, Guan; Xiaofeng, Ning; Yuanjuan, Gong (International Journal of Agricultural and Biological Engineering, 2014)
To find out a low temperature storage method for the maintenance of Hanfu apple firmness, crispness and moisture content, three storage methods in refrigerator, large cellar, and small cellar were experimented. Tests and comparisons were conducted for parameters including maximum absolute deformation, elastic modulus, firmness in compression test, and weight loss rate using mechanical characteristics monitoring and regular weighing during and after storage. Five testing groups with different pretreatments were arranged for refrigerator tests. The results showed that lower weight loss rates were achieved in two cellars than in the refrigerator; and difference between the large and small cellars was insignificant. However, cellar storage was only feasible for a relatively short term. Refrigeration storage with humidification sealing treatment yielded the optimal result in maintaining firmness, crispness and moisture of Hanfu apples, showing advantage in long-term storage.Keywords: Hanfu apple, low temperature storage, mechanical characteristics, weight loss rateDOI: 10.3965/j.ijabe.20140703.013Citation: Zhang B H, Guan S J, Ning X F, Gong Y J. Mechanical characteristics of Hanfu apple at low temperature. Int J Agric & Biol Eng, 2014; 7(3): 107-113.